Knowledge, Attitudes And Practices Towards COVID-19 among Medical Students in International Islamic University Malaysia: An Online Cross-Sectional Study - Abd Rahim, Ikhlas Solehah; Roslan, Muhammad Badrul Nizam; Mohamad Zaini, Nur Najihah; Kasim, Nur Syazwani; Mohd Yazid, Muhammad Izz Hilmi; Pasi, Hafizah; Nasreen, Hashima E (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: COVID-19 pandemic has caused a major impact to global public health including one of the high risk groups which is the medical students. This study was intended to assess knowledge, attitudes and practices (KAP) towards COVID-19 among medical students in International Islamic University Malaysia (IIUM). MATERIAL AND METHOD: An online cross-sectional study was conducted among 438 medical students of IIUM from 6th July 2020 to 9th July 2020. KAP towards COVID-19 was measured using a structured Malay and English version questionnaire consisting of 13 items on knowledge, 3 items on attitudes and 3 items on practices. RESULTS: The average correct response rate on knowledge was 85.4%. Only 12.1% of the students had correct knowledge on all items, and 1 in every 4 and 5 students had misconceptions on the clinical features and transmission of COVID-19. In term of attitudes towards COVID-19, majority of the respondents believed that COVID-19 would be effectively controlled (85%) and had faith that Malaysia could overcome the war against COVID-19 (99%). Most of the respondents practiced good towards COVID-19 in avoiding crowded places (90%), wearing face masks (95%) and practicing hand hygiene (91.6%). CONCLUSION: Although the results are positive towards KAP, only 1 in every 10 students responded correctly to all knowledge questions, and few proportions had misconceptions on the disease and did not maintain adequate practices. Policies aimed at appropriate health promotion activities may ensure empowering the medical students with adequate knowledge on all aspects of COVID-19, and practice properly following the standard operating procedure implemented by the government.